Double-ship-in-bottle catalyst for catalytic ozonation and preparation method of double-ship-in-bottle catalyst
By using the prepared double-ship catalyst in ozone catalytic oxidation, the bimetallic enhances interaction in the zeolite channel through sonication and ion exchange reaction of manganese salt and dealuminized zeolite, solving the problem of low CO2 selectivity in the prior art, and realizing the deep mineralization of VOCs into carbon dioxide.
Patent Information
- Application Number
- CN202411939814.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-26
AI Technical Summary
In the prior art, the CO2 selectivity of the zeolite-based catalyst for ozone catalytic oxidation is low, resulting in a high proportion of CO in the catalytic oxidation product, which is difficult to effectively reduce.
A method of preparing a double-ship catalyst in a bottle for ozone catalytic oxidation is adopted. By mixing the manganese salt solution with dealuminized zeolite and sonicating it to form Mn-zeolite, then undergoing ion exchange reaction with the second metal salt solution, and finally calcining at high temperature to obtain the catalyst, limiting the enhancement of the interaction of the bimetal in the zeolite channel.
By enhancing the interaction of bimetals in zeolite channels, Mn-OV-M asymmetric oxygen vacancies are generated, the conversion of ozone to reactive oxygen species is promoted, the selectivity of CO2 is improved, and the VOCs are deeply mineralized into non-toxic products such as carbon dioxide.
Smart Images

Figure CN119565665A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of ozone catalytic oxidation, and particularly relates to a double-boat catalyst in a bottle for ozone catalytic oxidation and a preparation method thereof. Background Art
[0002] Volatile organic compounds (VOCs) are seriously harmful to human health and the environment, and have been proven to be important precursors for the formation of ozone, secondary organic aerosols, and photochemical smog. Ozone catalytic oxidation technology has attracted widespread attention due to its effectiveness in oxidizing low concentrations of VOCs under mild conditions. Compared with catalytic combustion, the addition of ozone greatly reduces the reaction temperature and the activation energy required for the reaction. The ozone catalytic oxidation catalyst supported by zeolite at room temperature has a significant effect on the degradation of VOCs.
[0003] Zeolite is a carrier with a unique framework structure and pore system. Its crystal structure is a three-dimensional structure composed of silicon (aluminum) oxygen tetrahedra, with various sized cavities and pores in the structure. It is an advantageous carrier in ozone catalytic oxidation catalysts. However, taking Y zeolite as an example, its structure consists of almost spherical 13 Å supercages, which are interconnected in a tetrahedral manner through smaller pores with a diameter of 7.4 Å. The size of its guest molecules is also limited by the available space in these cavities. A reasonable approach is to expand the internal pore volume of zeolite so that it can serve as a carrier for large-volume metal catalysts. After the pore volume is expanded, the formation of mesopores completely surrounded by micropores has the additional advantage of easily forming carrier-metal bonds to reduce the mobility of metal particles and improve catalyst selectivity.
[0004] Although the currently used zeolite-based catalysts have achieved good catalytic efficiency and superior volatile organic pollutant removal rate, a common problem is that there is a high proportion of CO in the COx product of catalytic ozonation, which is a product that should be avoided in catalytic oxidation. The solution is to increase the selectivity of CO2, thereby reducing the concentration of CO in the product.
[0005] Existing studies have shown that MnOx catalysts have a high removal efficiency for VOCs and are one of the most promising non-precious metal catalysts. Compared with precious metals, manganese-based oxides have the advantages of large reserves, rich varieties, and low prices, although they do not have the best selectivity. Adding a second metal to Mn-based materials is an effective theoretical method to adjust the reactivity and selectivity by adjusting the binding strength and binding configuration of the intermediates on the catalytic surface.
[0006] In ozone catalytic oxidation, ozone decomposes in oxygen vacancies to produce active oxygen species, which have a stronger oxidizing ability for the intermediate product CO and can further oxidize CO to CO2, thereby improving the selectivity of CO2. However, the traditional impregnation method for loading bimetallic materials causes the random distribution of Mn and the second metal M, making it difficult for them to interact with each other, resulting in a lack of oxygen vacancies for the production of active oxygen species. Summary of the invention
[0007] In view of the above-mentioned problems of the prior art, the present invention provides a double-boat catalyst in a bottle for ozone catalytic oxidation and a preparation method thereof, which can overcome the defect of low CO2 selectivity of the ozone catalyst of the zeolite catalyst loaded with metal by the impregnation method in the prior art, and has good application prospects in the field of treating organic pollutants.
[0008] To achieve the above object, the present invention adopts the following technical solution: A method for preparing a double-boat catalyst in a bottle for ozone catalytic oxidation comprises the following steps: (1) mixing a manganese salt solution with a dealuminated zeolite and subjecting the mixture to ultrasonic treatment to obtain a first precursor; (2) pyrolyzing the first precursor in an inert atmosphere to obtain a second precursor (Mn-zeolite); (3) mixing the second precursor and a metal salt solution to perform an ion exchange reaction to obtain a third precursor; (4) calcining the third precursor at high temperature to obtain the catalyst.
[0009] Preferably, the molar ratio of the manganese salt in step (1) to the metal salt in step (3) is 1:3 to 3:1.
[0010] Preferably, the dealuminated zeolite in step (1) is prepared by placing a dried zeolite in an acid solution for dealumination. More preferably, the zeolite is one of beta zeolite, Y zeolite or ZSM-5, and the silicon-to-aluminum ratio in the zeolite is greater than 5.
[0011] Preferably, the acid solution is a 0.5-2 mol / L nitric acid solution.
[0012] Preferably, the volume ratio of the zeolite to the acid solution is 1:(8-12).
[0013] Preferably, the dealumination reaction temperature is 60-100°C.
[0014] Preferably, the dealumination reaction time is 4 to 6 hours.
[0015] Preferably, the dealumination reaction further comprises the steps of washing with water and drying after the reaction is completed.
[0016] Preferably, the manganese salt in step (1) is manganese acetate, manganese nitrate, manganese chloride or manganese sulfate.
[0017] Preferably, the solvent of the manganese salt solution in step (1) is ethanol, methanol or butanol.
[0018] Preferably, the concentration of the manganese salt solution in step (1) is 50-200 μmol mL -1 .
[0019] Preferably, the ultrasonic treatment time in step (1) is 180-270 min.
[0020] Preferably, the pyrolysis temperature in step (2) is 450-550°C.
[0021] Preferably, the pyrolysis time in step (2) is 70 to 110 minutes.
[0022] Preferably, the metal salt solution in step (3) is a salt solution of Cu, Co, Ce or Fe.
[0023] Preferably, the concentration of the metal salt solution in step (3) is 0.1-1 mol / L.
[0024] Preferably, the volume ratio of the second precursor in step (3) to the metal salt solution is 1:(50-80).
[0025] Preferably, the temperature of the ion exchange reaction in step (3) is 70°C.
[0026] Preferably, the ion exchange reaction time in step (3) is 3 to 6 hours.
[0027] Preferably, the ion exchange reaction in step (3) further comprises a step of washing with deionized water after the reaction is completed.
[0028] Preferably, the metal salt solution in step (3) is acetate, sulfate, nitrate or chloride.
[0029] Preferably, the calcination temperature in step (4) is 500-550°C.
[0030] Preferably, the calcination time in step (4) is 180 min.
[0031] The second object of the present invention is to provide a double-boat catalyst in a bottle for ozone catalytic oxidation prepared by the above preparation method.
[0032] The beneficial effects of the present invention are: The zeolite-encapsulated double-boat-in-a-bottle catalyst was prepared to confine the bimetallic atoms in the zeolite pores to enhance the interaction and generate M1-OV-M2 asymmetric oxygen vacancies, thereby promoting the conversion of ozone into active oxygen species for catalytic oxidation of VOCs and improving CO2 selectivity.
[0033] The zeolite-encapsulated Mn-M double-boat-in-a-bottle metal catalyst of the present invention uses zeolite with high specific surface area and moderate pore size as a carrier, firstly adopts the dealumination method to expand the internal cavity of the zeolite to form a mesoporous zeolite material surrounded by micropores, and first introduces a Mn metal precursor into the pores, and adopts the ship-in-a-bottle method to make a Mn-zeolite ship-in-a-bottle, and then uses excess unreacted Mn as a template, and adopts post-ion exchange to replace the second metal M to the position of the template Mn, forming a catalyst similar to the double-boat-in-a-bottle. The lattice oxygen of the dealuminated zeolite carrier forms a metal-carrier bond with Mn, anchoring the position of Mn and the second metal. The change in the coordination environment enhances the interfacial effect between the Mn-M metal nanoparticles, confining the bimetallic in the zeolite pores to enhance the interaction to produce Mn-OV-M asymmetric oxygen vacancies, promoting the conversion of ozone to active oxygen species, and increasing the activity of oxygen vacancies, thereby improving the utilization efficiency of active oxygen species produced by O3 during the catalytic oxidation process. This further promotes the selectivity of CO2 in the ozone catalytic oxidation of VOCs products, allowing VOCs to be deeply mineralized into non-toxic products such as carbon dioxide. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a graph showing the conversion efficiency of the catalyst prepared in Example 1 for toluene.
[0035] Figure 2 This is a graph showing the conversion efficiency of the catalyst prepared in Example 2 for toluene.
[0036] Figure 3 This is a graph showing the conversion efficiency of the catalyst prepared in Example 3 for toluene.
[0037] Figure 4 It is a comparative chart of the selectivity of the catalysts prepared in Examples 1-3 for carbon dioxide.
[0038] Figure 5 This is the characterization result of H2-TPR of the catalyst in Example 5. DETAILED DESCRIPTION
[0039] The following detailed description of exemplary embodiments of the present invention refers to the accompanying drawings. Although these exemplary embodiments are described in sufficient detail to enable those skilled in the art to implement the present invention, it should be understood that other embodiments may be implemented and various changes may be made to the present invention without departing from the spirit and scope of the present invention. The following more detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed invention, but is merely for illustration and does not limit the description of the features and characteristics of the present invention, in order to propose the best way to perform the present invention and to enable those skilled in the art to implement the present invention. Therefore, the scope of the present invention is limited only by the appended claims. Example 1
[0040] After grinding and crushing the beta zeolite, sieve it into 20-40 mesh granular powder and dry it. Prepare 1 mol / L nitric acid solution, put the above zeolite and the prepared nitric acid solution into a three-necked flask at a solid-liquid ratio of 1:10, stir and react in a reflux device at 80℃ for 6 hours, and after the reaction, wash the sample with water 5 times and dry it overnight. Add 0.11 g of manganese acetate tetrahydrate to 5 mL of ethanol to prepare 150 μmol mL -1 Mn(CH3COO)2 ethanol solution: 1.7 mL of the prepared Mn(CH3COO)2 ethanol solution was added to 250 mg of expanded pore beta zeolite and ultrasonicated for 250 min.
[0041] After vacuum drying overnight, the above material was pyrolyzed at 500 °C for 90 min in an argon atmosphere and then taken out to obtain Mn-zeolite.
[0042] Prepare a 0.1 mol / L copper nitrate aqueous solution, mix Mn-zeolite and copper nitrate solution in a solid-liquid ratio of 1:60, heat and stir to replace unreacted Mn ions with Cu ions, wash with deionized water 10 times, and dry at 110°C overnight.
[0043] The obtained powder was calcined at 550° C. for 180 min in air atmosphere and then taken out.
[0044] Catalyst performance evaluation: Figure 1 , 4 As shown, the reaction temperature is 30°C, the catalyst mass is 0.1g, the gas flow rate is 0.5L / min, the toluene inlet concentration is 200ppm, the ozone inlet concentration is 3000ppm, the toluene conversion rate is 100%, the CO2 conversion rate is 72%, no ozone is detected at the outlet, and there is no obvious change in the catalyst performance after running for 30 hours. Example 2
[0045] After grinding and crushing the Y zeolite, sieve it into 2-40 mesh granular powder and dry it. Prepare 2 mol / L nitric acid solution, put the above zeolite and the prepared nitric acid solution into a three-necked flask at a solid-liquid ratio of 1:8, stir and react in a 60℃ reflux device for 6 hours. After the reaction, wash the sample with water 5 times and dry it overnight. Add manganese nitrate to 5 mL methanol to prepare 200 μmol mL -1 Mn(NO3)2 methanol solution: 1 mL of the prepared Mn(NO3)2 methanol solution was added to 250 mg of the expanded pore zeolite and ultrasonicated for 270 min.
[0046] After vacuum drying overnight, the above material was pyrolyzed at 550 °C for 110 min in an argon atmosphere and then taken out to obtain Mn-zeolite.
[0047] A 0.1 mol / L aqueous solution of cobalt nitrate was prepared, and Mn-zeolite and cobalt nitrate solution were mixed at a solid-liquid ratio of 1:80, and then heated and stirred to replace unreacted Mn ions with Co ions. After washing with deionized water 10 times, it was dried at 110°C overnight.
[0048] The obtained powder was calcined at 500° C. for 180 min in air atmosphere and then taken out.
[0049] The catalyst performance evaluation was the same as in Example 1. The results are as follows Figure 2 , 4 shown. Example 3
[0050] After grinding and crushing the ZSM-5 zeolite, sieve it into 20-40 mesh granular powder and dry it. Prepare 0.5 mol / L nitric acid solution, put the above zeolite and the prepared nitric acid solution into a three-necked flask at a solid-liquid ratio of 1:12, stir and react in a 100℃ reflux device for 4 hours, and after the reaction, wash the sample with water 5 times and dry it overnight. Add manganese chloride to 5 mL butanol to prepare 50 μmol mL -1 MnCl2 butanol solution; 1.7 mL of the prepared Mn Cl2 butanol solution was added to 250 mg of the expanded pore zeolite and ultrasonically treated for 180 min.
[0051] After vacuum drying overnight, the above material was pyrolyzed at 450 °C for 70 min in an argon atmosphere and then taken out to obtain Mn-zeolite.
[0052] A 1 mol / L aqueous solution of cerium nitrate was prepared, and Mn-zeolite and cerium nitrate solution were mixed at a solid-liquid ratio of 1:50, and then heated and stirred to replace unreacted Mn ions with Ce ions. After washing with deionized water 10 times, it was dried at 110°C overnight.
[0053] The obtained powder was calcined at 500° C. for 180 min in air atmosphere and then taken out.
[0054] The catalyst performance evaluation was the same as in Example 1. The results are as follows Figure 3 , 4 shown. Example 4
[0055] After grinding and crushing the beta zeolite, sieve it into 20-40 mesh granular powder and dry it. Prepare 1 mol / L nitric acid solution, put the above zeolite and the prepared nitric acid solution into a three-necked flask at a solid-liquid ratio of 1:10, stir and react in a reflux device at 80℃ for 6 hours, and after the reaction, wash the sample with water 5 times and dry it overnight. Add 0.11 g of manganese acetate tetrahydrate to 5 mL of ethanol to prepare 150 μmol mL -1 Mn(CH3COO)2 ethanol solution: 1.7 mL of the prepared Mn(CH3COO)2 ethanol solution was added to 250 mg of expanded pore beta zeolite and ultrasonicated for 250 min.
[0056] After vacuum drying overnight, the above material was pyrolyzed at 500 °C for 90 min in an argon atmosphere and then taken out to obtain Mn-zeolite.
[0057] A 0.1 mol / L aqueous solution of ferric nitrate was prepared, and Mn-zeolite and ferric nitrate solution were mixed at a solid-liquid ratio of 1:60, and then heated and stirred to replace unreacted Mn ions with Fe ions. After washing with deionized water 10 times, it was dried at 110°C overnight.
[0058] The obtained powder was calcined at 550°C for 180 min in an air atmosphere and then taken out to obtain Fe-Mn / beta.
[0059] As a control, the above method was used, except that the Mn / beta catalyst was obtained by direct secondary calcination instead of using an aqueous ferric nitrate solution for replacement.
[0060] The prepared catalysts Fe-Mn / beta and Mn / beta were characterized by H2-TPR. Figure 5 As shown. A signal value near 472 °C can be detected in Fe−Mn / beta, which may correspond to the reduction of some FeOx species. Since the first reduction peak of a catalyst usually determines its reducibility, it can be seen that the position of the first reduction peak in Fe-Mn / beta moves to a lower temperature compared with Mn / beta and Fe-Mn / beta, indicating that the increase of Fe improves the reducibility of metal oxides. In addition, unlike Mn / beta, a reduction peak near 359 °C was observed in Fe-Mn / beta. The results show that the addition of the second metal increases the electron transfer between the Fe-Mn composite oxides and changes the reducibility of the catalyst, further confirming the interaction between the second metal and Mn.
Claims
1. A method for preparing a double-boat catalyst in a bottle for ozone catalytic oxidation, characterized in that: The steps include: (1) mixing a manganese salt solution with a dealuminated zeolite and subjecting the mixture to ultrasonic treatment to obtain a first precursor; (2) pyrolyzing the first precursor in an inert atmosphere to obtain a second precursor; (3) mixing the second precursor and a metal salt solution to perform an ion exchange reaction to obtain a third precursor; (4) calcining the third precursor at high temperature to obtain the catalyst.
2. The preparation method according to claim 1, characterized in that: The molar ratio of the manganese salt in step (1) to the metal salt in step (3) is 1:3 to 3:
1.
3. The preparation method according to claim 1, characterized in that: The dealuminated zeolite in step (1) is prepared by placing a dried zeolite in an acid solution for dealumination reaction; more preferably, the zeolite is one of beta zeolite, Y zeolite or ZSM-5, and the silicon-to-aluminum ratio in the zeolite is above 5.
4. The preparation method according to claim 1, characterized in that: The manganese salt described in step (1) is manganese acetate, manganese nitrate, manganese chloride or manganese sulfate.
5. The preparation method according to claim 1, characterized in that: The duration of the ultrasonic treatment in step (1) is 180 to 270 minutes.
6. The preparation method according to claim 1, characterized in that: The pyrolysis temperature in step (2) is 450-550° C., and the pyrolysis time is 70-110 min.
7. The preparation method according to claim 1, characterized in that: The metal salt solution described in step (3) is a salt solution of Cu, Co, Ce or Fe.
8. The preparation method according to claim 1, characterized in that: The metal salt solution in step (3) is acetate, sulfate, nitrate or chloride.
9. The preparation method according to claim 1, characterized in that: The calcination temperature in step (4) is 500-550°C, and the calcination time is 180 minutes.
10. Double-boat catalyst in a bottle for ozone catalytic oxidation prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Bifunctional catalyst and preparation method thereof
CN107652151A
Catalyst for catalytic ozonation of volatile organic compounds and preparation method thereof
CN113145161A
Composite manganese-based catalyst as well as preparation method and application thereof
CN116689023A
Zeolite catalyst with improved NOX reduction in SCR
US20070134146A1